The monologic imagination - Tomlinson, Matt 1970-; Millie, Julian 1967- (New York, NY, United States of America Oxford University Press, 2017)
The pioneering work of Bakhtin has led scholars to see all discourse as "dialogical." Contributors to this volume argue that something is overlooked with this focus. Many speakers, especially in political and religious contexts, craft monologues-single-voiced statements to which the only expected response is agreement or faithful replication.
Introduction : Imagining the Monologic / Matt Tomlinson -- Cultural Replication : The Source of Monological and Dialogical Models of Culture / Greg Urban -- Dialogic Prophecies and Monologic Vision / Jon Bialecki -- Monologue and Dialogism in Highland New Guinea Verbal Art / Alan Rumsey -- Discussion : Is It Monologic? Is It Dialogic? What Difference Does It Make? / Don Kulick -- "With Unity We Will Be Victorious!" : A Monologic Poetics of Political "Conscientization" within the Cuban Revolution / Kristina Wirtz -- From Neighborhood Talk to Talking for the Neighborhood / Zane Goebel -- Monologue and Authority in Iran : Ethnic and Religious Heteroglossia in the Islamic Republic / James Barry -- Discussion : Diving into the Gap : "Words," "Voices," and the Ethnographic Implications of Linguistic Disjuncture / Krista E. Van Vleet -- Acting with One Voice : Producing Unanimism in Algerian Reformist Theater / Jane E. Goodman -- Creedal Monologism and Theological Articulation in the Mennonite Central Committee / Philip Fountain -- The Public Metaculture of Islamic Preaching / Julian Millie -- Discussion : The Monologic Imagination of Social Groups / Courtney Handman -- Conclusion : Religious and Political Terrain of the Monologic Imagination / Matt Tomlinson and Julian Millie.
Includes bibliographical references and index.
Keywords: Dialogue analysis -- Political aspects; Monologues; Discourse analysis -- Political aspects; Communication -- Political aspects; Anthropological linguistics